The role of inflammation in suicidal behaviour - Brundin, L. (Acta Psychiatr Scand, 2015)
OBJECTIVE: Over the past decade, clinical data have accumulated showing that inflammation might contribute to the pathophysiology of suicide. To evaluate the associations and to identify the support for pathways linking inflammatory processes with suicidal behaviour, a comprehensive review of the literature was undertaken. METHOD: The search terms ‘cytokine’, ‘risk factors’, ‘kynurenine’, ‘asthma’, ‘allergy’, ‘autoimmunity’, ‘traumatic brain injury’, ‘infection’ along with the terms ‘inflammation’ and ‘suicide’ were entered into PubMed, and a thorough analysis of the publications and their reference lists was performed. RESULTS: The effects of inflammation on mood and behaviour could partially be mediated by kynurenine pathway metabolites, modulating neuroinflammation and glutamate neurotransmission. At the same time, the triggers of the inflammatory changes documented in suicidal patients may be attributed to diverse mechanisms such as autoimmunity, neurotropic pathogens, stress or traumatic brain injury. CONCLUSION: Targeting the inflammatory system might provide novel therapeutic approaches as well as potential biomarkers to identify patients at increased risk. For the goal of improved detection and treatment of suicidal individuals to be achieved, we need to develop a detailed understanding of the origin, mechanisms and outcomes of inflammation in suicidal behaviour.